[PP.24.07] AGENESIS OF RIGHT CORONARY ARTERY DIAGNOSED IN A 48 YEAR-OLD WOMAN. (September 2017) - Dediu, G.; Stoica, A.; Balaceanu, A.; Diaconu, C.; Aron, G.; Dina, I.
Abstract : Objective: The presence of a single coronary artery pathology is very rare, the reported incidence of this anomaly among patients who received angiography being between 0.6 to 1.3%. The association of this disease with other conditions which increases the degree of myocardial ischemia gives unsatisfactory long-term prognosis. Design and method: Case presentation. A 48-year-old woman, overweight, presented with daytime sleepiness and palpitations. Physical examination did not show significant findings. Figure. No caption available. Results: Laboratory investigations, ECG, chest radiography and cardiac ultrasound were normal. Epworth questionnaire score was 12 points. Holter ECG: 134 ventricular extrasystoles. Sleep apnea syndrome was suspected and cardiorespiratory polygraphy was performed, which showed severe obstructive sleep apnea. Continuous positive airway pressure (CPAP) and beta blockers therapy was started, but the patient continued to have palpitations. An electrocardiogram (ECG) stress test was performed, with Bruce protocol. Exercise ECG was positive for ischemia, the patient complaining of chest pain. Coronarography was done, which revealed the agenesis of the right coronary artery, with normal epicardial coronary arteries. CT angiography confirmed the absence of the right coronary artery, its territory being vascularized by the terminal branch of circumflex artery, extended in the right atrioventricular groove (Panel A, B, C, D). Conclusions: Conclusions. Long term prognosis of this patient is not favorable, due to agenesis of the right coronary artery associated with severe sleep apnea syndrome. Sleep apnea syndrome is a known aggravating factor for myocardial ischemia and a risk factor for sudden cardiac death during sleep.